P057 All- cause mortality in patients with invasive Candidiasis or candidemia from an interim analysis of a Phase 3 Open-label Study (FURI). (20th September 2022) - Prattes, Juergen; King, Thomas; Azie, Nkechi; Angulo, David
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM: Background: There are limited oral treatment options for patients with high-mortality fungal infections such as candidemia or invasive candidiasis who fail currently available antifungals or have an infection caused by resistant organisms. Ibrexafungerp is an investigational broad-spectrum glucan synthase inhibitor with activity against Candida species, including azole- and echinocandin-resistant strains. A Phase 3 open-label, single-arm study of ibrexafungerp (FURI; NCT03059992) is ongoing for the treatment of patients intolerant of, or with invasive fungal disease refractory to, standard antifungal therapy. We present an interim analysis of all-cause mortality within 30 days post-treatment from the FURI study by fungal disease type for patients with candidemia or invasive candidiasis, who completed therapy up until October 2021. Methods: FURI patients are eligible for enrolment if they have proven or probable: severe mucocutaneous candidiasis or invasive candidiasis, or candidemia, with documented evidence of failure, intolerance, or toxicity related to a currently approved standard-of-care antifungal treatment; or patients who cannot receive approved oral antifungal options (eg, due to susceptibility), and continued IV antifungal therapy is clinically undesirable or unfeasible. Patients were followed through 30 days post-treatment for all-cause mortality. Results: Out of the 113 patients who completed therapy in the FURI study through October 2021, 56 (50%) had invasive candidiasis or candidemia and were treated with ibrexafungerp. The most common infections in this group were candidemia (15/56, 26.8%), intra-abdominal infection (13/56, 23.2%), and bone infection (10/56, 17.9%). Overall survival within 30 days post-treatment in this group of 56 patients was 94.6%. Of the 56 patients with candidemia or invasive candidiasis, three (5.3%) died within 30 days after completion of treatment with ibrexafungerp, a fourth died at 31 days, a fifth died at 50 days, and a sixth died at 56 days. The mean age of the expired patients was 56 years. All 4 patients had candidemia (3 with C. parapsilosis and 1 with C. albicans ), and 2 had intra-abdominal candidiasis, (both with C. glabrata ). The average time on therapy with ibrexafungerp was 15.7 days. The mean time to death post-treatment for these patients was 27 days (median, 21 days). In five cases, the deaths were due to causes other than the underlying fungal disease. For the other case, the cause of death was not disclosed. Conclusions: Analysis of all-cause mortality in these patients from the FURI study indicates that oral ibrexafungerp provides a favorable therapeutic response in patients with challenging fungal diseases and limited treatment options.